2017
DOI: 10.1039/c6ob02577c
|View full text |Cite
|
Sign up to set email alerts
|

Chemical modification improves the stability of the DNA aptamer GBI-10 and its affinity towards tenascin-C

Abstract: Aptamers are useful tools in molecular imaging due to their numerous attractive properties, such as excellent affinity and selectivity to diverse types of target molecules and biocompatibility. We carried out structure-activity relationship studies with the tenascin-C (TN-C) binding aptamer GBI-10, which is a promising candidate in tumor imaging. To increase the tumor targeting ability and nuclease resistance under physiological conditions, systematic modifications of GBI-10 with single and multiple 2'-deoxyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…Based on our previous experiences, selectively combinations of activity-enhanced sites are more likely to further improve the performance of the aptamer. 22 , 23 , 24 Additionally, 2′-dI offers a huge advantage for diagnostic utility, and when 2′-dI is incorporated at position 24, it can enhance the bioactivity of AS1411. To further optimize AS1411, we incorporate isoT at the 6 th and 12 th positions simultaneously (FCL-I).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on our previous experiences, selectively combinations of activity-enhanced sites are more likely to further improve the performance of the aptamer. 22 , 23 , 24 Additionally, 2′-dI offers a huge advantage for diagnostic utility, and when 2′-dI is incorporated at position 24, it can enhance the bioactivity of AS1411. To further optimize AS1411, we incorporate isoT at the 6 th and 12 th positions simultaneously (FCL-I).…”
Section: Resultsmentioning
confidence: 99%
“…Based on experimental results, D-/L-isoT increased the aptamer activities in a stronger way. We have used D-/L-isoNA to modify more than 5 different aptamers, including TBA, 21 AS1411, 25 GBI-10, 22 , 23 , 24 BC-15, and DT-2 (unpublished data). Some of these are G-quadruplexes, and some are not.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, according to Rozemblum et al, backbone modifications can reduce the ability of polymerase to amplify the DNA in the PCR amplification step [ 53 ]. Conversely, the post-SELEX strategies introduce modifications to aptamers after the selection, during the solid-phase chemical synthesis of individual aptamers [ 54 ]. To solve the problem of renal filtration, aptamers are generally linked to polyethylene glycol (PEG), cholesterol, or proteins.…”
Section: Aptamersmentioning
confidence: 99%
“…The SMART probe had a better affinity and specificity to several tumors like glioma, prostate cancer, cervical cancer, and lung cancer cells [77]. The next generation of TN-C aptamer was GBI-10 and shown that it can bind several TN-C peptides in vitro [75,78]. The most important part of the fact that GBI-10 can target several binding sites of TN-C is the ability to address multiple splice variants at the same time.…”
Section: Tenascin-cmentioning
confidence: 99%